Green composite corrosion inhibitor for inhibiting corrosion of carbon steel
By using green composite corrosion inhibitors composed of chitosan, curcumin and geraniol, the problems of existing corrosion inhibitors are solved, and the low-cost, environmentally friendly and efficient corrosion inhibition effect of carbon steel is achieved. .
Patent Information
- Application Number
- CN202411553049.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
Existing corrosion inhibitors have toxicity, high costs and environmental pollution problems, making them difficult to adapt to mass production and environmental protection requirements.
A green composite corrosion inhibitor with chitosan, curcumin and geraniol as the main components is mixed into a solution and used in hydrochloric acid to inhibit the corrosion of carbon steel.
It has achieved significant inhibition of the corrosion of Q235 carbon steel, which is low-cost, simple in preparation, safe and non-toxic, biodegradable, suitable for mass production and environmental protection requirements.
Smart Images

Figure CN119411136A_ABST
Abstract
Description
Background Art
[0001] Carbon steel among metal materials is widely used in the base material of power transmission and transformation equipment in power systems. It is cheap, easy to obtain, and has good mechanical properties. It is an essential material for many large metal equipment and buried metals. Carbon steel is easy to corrode. It needs to be painted or plated with an anti-rust layer before use. Before painting or plating, the surface rust and oil stains must be cleaned, and the surface must be cleaned by pickling, ultrasonic and other methods. Measures must be taken during operation to inhibit corrosion. It is necessary to have a cleaning speed for the oxide on the steel surface and protect the steel matrix from excessive corrosion and pickling defects. The current common measure is to add corrosion inhibitors, but most of the existing corrosion inhibitors are toxic and costly, and cannot be mass-produced.
[0002] Existing corrosion inhibitors are mainly divided into organic corrosion inhibitors and inorganic corrosion inhibitors. At present, organic corrosion inhibitors on the market can be basically divided into imidazoline corrosion inhibitors, quaternary ammonium salt corrosion inhibitors, Schiff base corrosion inhibitors and some other heterocyclic compounds. Most organic compounds can be adsorbed on the metal surface through functional groups such as nitrogen, π bonds, double bonds, etc., thereby inhibiting the occurrence of electrochemical corrosion. However, these substances are expensive, and the actual amount of addition required when exerting a corrosion inhibition effect is large, which is not suitable for mass production and use. The principle of most inorganic corrosion inhibitors is to oxidize the metal surface to form a protective layer or precipitate on the metal surface to inhibit metal corrosion. The use of inorganic corrosion inhibitors has high environmental requirements, and vice versa may aggravate corrosion. In addition, common inorganic corrosion inhibitors such as chromates, molybdates, phosphates and silicates are prone to cause environmental pollution, and their use has been restricted in recent years. Therefore, it is urgent to develop a green and environmentally friendly corrosion inhibitor for use. Summary of the invention
[0003] The purpose of the present invention is to propose a green composite corrosion inhibitor for inhibiting carbon steel corrosion, so as to alleviate a series of technical problems caused by Q235 carbon steel corrosion in a green and environmentally friendly way.
[0004] The technical solution of the present invention is a green composite corrosion inhibitor for inhibiting carbon steel corrosion, which consists of chitosan, curcumin and geraniol. The chitosan, curcumin and geraniol are mixed into a solution with a concentration of 1.5-2 mM chitosan, 1.5-2 mM curcumin and 1.5-2 mM geraniol.
[0005] The preferred concentrations are: chitosan 1.5 mM, curcumin 1.5 mM, geraniol 2 mM.
[0006] The beneficial effects of the present invention are as follows: the three components of the corrosion inhibitor of the present invention are all derived from natural animals and plants, and compared with existing corrosion inhibitors, it has the advantages of low cost, simple preparation, safety, non-toxicity, biodegradability, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1The corrosion inhibition rate image of the Q235 carbon steel specimen in Example 1 in a 20-day weight loss experiment in 1M hydrochloric acid with the addition of corrosion inhibitor Chi-Ger-Cur; Figure 2 The Fe and Fe of the Q235 carbon steel specimen in Example 1 were measured in 1M hydrochloric acid with or without the addition of the corrosion inhibitor Chi-Ger-Cur. 2+ Content images; Figure 3 The SEM images of the Q235 carbon steel specimens in Example 1 before and after 20 days in 1M hydrochloric acid with or without the addition of the corrosion inhibitor Chi-Ger-Cur (a: CK group at 0 days; b: CK group at 20 days; c: corrosion inhibitor group at 0 days; d: corrosion inhibitor group at 20 days); Figure 4 The EDS images of the Q235 carbon steel specimen in Example 1 before and after 20 days in 1M hydrochloric acid with or without the addition of the corrosion inhibitor Chi-Ger-Cur (a: corrosion inhibitor group at 0 days; b: corrosion inhibitor group at 20 days); Figure 5 The impedance spectra of the Q235 carbon steel specimen in Example 1 before and after 15 days in 1M hydrochloric acid with or without the addition of corrosion inhibitor Chi-Ger-Cur (a: 0 days; b: 5 days; c: 10 days; d: 15 days); Figure 6 The Tafel curves of the Q235 carbon steel specimen in Example 1 before and after 15 days in 1M hydrochloric acid with or without the addition of the corrosion inhibitor Chi-Ger-Cur (a: 0 days; b: 5 days; c: 10 days; d: 15 days); Figure 7 The XPS graphs of the Q235 carbon steel specimens in Example 1 before and after 20 days in 1M hydrochloric acid with or without the addition of the corrosion inhibitor Chi-Ger-Cur (a: CK group at 0 days; b: CK group at 20 days; c: corrosion inhibitor group at 0 days; d: corrosion inhibitor group at 20 days); Figure 8 This is the XPS Fe2p fine spectrum of the Q235 carbon steel specimen in Example 1 after 20 days in 1M hydrochloric acid without adding corrosion inhibitor Chi-Ger-Cur. DETAILED DESCRIPTION
[0008] Example 1 A green composite corrosion inhibitor Chi-Ger-Cur for inhibiting corrosion of Q235 carbon steel has the following components and concentrations: chitosan 1.5 mM, geraniol 2 mM, and curcumin 1.5 mM.
[0009] Calculate the weight of the three components required per liter based on the content of 1.5 mmol chitosan, 2 mmol geraniol, and 1.5 mmol curcumin per liter, and weigh the required weight in multiples according to the required solution volume (in liters). After weighing, add it to a hydrochloric acid solution with a molar concentration of 1M. The volume of the hydrochloric acid solution required is the volume corresponding to the weighed weight (the amount of chitosan, geraniol, and curcumin added relative to the solution volume does not cause much volume change, so the volume change is ignored here). Place a Q235 carbon steel sheet in a hydrochloric acid solution containing the composite corrosion inhibitor Chi-Ger-Cur, and monitor the weight loss of the Q235 carbon steel sheet every 5 days for 20 days. The weight loss experiment uses a Q235 carbon steel specimen, and 1M HCl without any corrosion inhibitor is used as a blank control. Figure 1 As shown in the figure, compared with the control group, the Q235 carbon steel sheet in 1M HCl with the addition of corrosion inhibitor Chi-Ger-Cur has a significant corrosion inhibition effect, and the average corrosion inhibition rate is as high as 71.54% at 20 days.
[0010] After adding the corrosion inhibitor Chi-Ger-Cur to the 1M HCl solution, the Fe and Fe in the 1M HCl solution were monitored every 5 days using the o-phenanthroline spectrophotometer. 2+ Content, monitoring time 20d.
[0011] The monitoring results are as follows: Figure 2 As shown in the figure, after adding the corrosion inhibitor Chi-Ger-Cur, it can be found that as time goes by, the Fe and Fe 2+ The content also increased, but the Fe and Fe 2+ The content was the lowest and significantly different from that of the CK group. The Fe and Fe 2+ The content of Fe in the Chi-Ger-Cur treatment group was lower than that in the CK group within 20 days. 2+ The contents were 0.21g and 0.08g, respectively, which were lower than the 0.71g Fe and 0.39g Fe released by the CK group. 2+ , indicating that the Chi-Ger-Cur treatment group has a certain corrosion inhibition effect.
[0012] The Q235 carbon steel sheet treated with the corrosion inhibitor Chi-Ger-Cur was characterized by scanning electron microscopy (SEM), and some chemical elements of the Q235 carbon steel sheet before and after corrosion were quantified by EDS.
[0013] The characterization results are as follows: Figure 3As shown in the figure, the surface of the Q235 carbon steel sheet in the control group and the corrosion inhibitor group was relatively flat at 0d, with no obvious signs of corrosion. After the control group and the corrosion inhibitor group were immersed in 1M HCl for 20d, the control group had dense corrosion products and obvious deep pits, while the corrosion inhibitor group had certain corrosion products but basically no obvious deep pits, which proved that the addition of compound corrosion inhibitors can significantly inhibit the corrosion of Q235 carbon steel.
[0014] like Figure 4 As shown in the figure, after EDS energy spectrum analysis, the O element content of the O235 carbon steel specimen treated with Chi-Ger-Cur was low after 20 days, while the O element content of the control group was very high. The main component of rust is iron oxide. Therefore, the rust in the control group is more than that in the Chi-Ger-Cur treatment group, which also shows the effect of Chi-Ger-Cur corrosion inhibitor to a certain extent.
[0015] Electrochemical impedance spectroscopy (EIS) and Tafel tests were performed: a traditional three-electrode system was used, with the reference electrode and counter electrode being saturated calomel electrode (SCE) and carbon felt electrode, respectively, and the working electrode being Q235 carbon steel sheet. Before the formal test, a 5-minute open circuit potential (OPC) test was performed to allow it to reach a stable state, and then an electrochemical impedance scan was performed at a frequency of 100kHz to 10mHz. The polarization test was performed at a scan rate of 0.2mv / s relative to the open circuit potential ±500mV.
[0016] like Figure 5 As shown in the figure, after adding the corrosion inhibitor Chi-Ger-Cur to the 1M HCl solution, the impedance radius of the Chi-Ger-Cur group and the control group gradually increased with time, indicating that the increase in resistance led to a decrease in corrosion current. The impedance radius of the Chi-Ger-Cur group was larger than that of the control group at 10d, and the impedance radius was still significantly larger than that of the control group at 15d, indicating that Chi-Ger-Cur has good corrosion inhibition effect and long corrosion inhibition time, and can be used as a new natural green corrosion inhibitor.
[0017] like Figure 6 As shown in the figure, after adding the corrosion inhibitor Chi-Ger-Cur to the 1M HCl solution, the CK group was compared with the Chi-Ger-Cur group. It can be found that the Tafel curve of the Chi-Ger-Cur group moved significantly to the right, that is, the corrosion potential shifted positively, and the corrosion current density decreased, indicating that the addition of the Chi-Ger-Cur corrosion inhibitor increased the polarization resistance of the carbon steel surface and inhibited corrosion, that is, the Chi-Ger-Cur group had a certain corrosion inhibition effect.
[0018] The Q235 carbon steel sheets treated with the corrosion inhibitor Chi-Ger-Cur and untreated were tested by XPS, and Avantage was used for peak fitting after the test.
[0019] like Figure 7 As shown in the figure, the XPS peak of the control group after 20 days of treatment is significantly different from that of 0 days, and after peak fitting, Fe oxides can be clearly detected. Figure 8 The fine spectrum shows that different Fe oxides were measured on the Q235 test piece without Chi-Ger-Cur corrosion inhibitor, including FeO, Fe2O3, Fe3O4, and Fe 2+ :Fe 3+ The ratio of Chi-Ger-Cur to the XPS peak after 20 days of treatment is not much different from that after 0 days, and the content of Fe oxide that can be detected is very small. Therefore, it shows that Chi-Ger-Cur has good corrosion inhibition effect and long corrosion inhibition time, and can be used as a new natural green corrosion inhibitor.
[0020] Example 2 A green composite corrosion inhibitor Chi-Ger for inhibiting corrosion of Q235 carbon steel has the following components and concentrations: chitosan 1.5 mM, geraniol 2 mM.
[0021] A hydrochloric acid solution containing the corrosion inhibitor Chi-Ger was prepared according to the weighing and proportioning method of Example 1, and a Q235 carbon steel sheet was placed in the hydrochloric acid solution. The weight loss of the Q235 carbon steel sheet was monitored every 5 days for 20 days. Compared with the control group, the addition of the corrosion inhibitor Chi-Ger had a significant corrosion inhibition effect on the Q235 carbon steel sheet in 1M HCl, and the average corrosion inhibition rate was 46.81% at 20 days.
[0022] After adding the corrosion inhibitor Chi-Ger to the 1M HCl solution, the Fe and Fe in the 1M HCl solution were monitored every 5 days using the o-phenanthroline spectrophotometer. 2+ The monitoring time is 20 days. The monitoring results are as follows: After adding the corrosion inhibitor Chi-Ger, the Fe and Fe 2+ The content of Fe and Fe 2+ The contents were 0.29g and 0.09g, respectively, which were lower than the 0.71g Fe and 0.39g Fe released by the CK group. 2+ , indicating that the Chi-Ger treatment group has a certain corrosion inhibition effect.
[0023] Example 3 A green composite corrosion inhibitor Ger-Cur for inhibiting carbon steel corrosion has the following components and concentrations: 2 mM geraniol and 1.5 mM curcumin.
[0024] A hydrochloric acid solution containing the corrosion inhibitor Ger-Cur was prepared according to the weighing and proportioning method of Example 1, and a Q235 carbon steel sheet was placed in the hydrochloric acid solution. The weight loss of the Q235 carbon steel sheet was monitored every 5 days for 20 days. Compared with the control group, the addition of the corrosion inhibitor Ger-Cur had a significant corrosion inhibition effect on the Q235 carbon steel sheet in 1M HCl, and the average corrosion inhibition rate was 51.45% at 20 days.
[0025] After adding the corrosion inhibitor Chi-Cur to the 1M HCl solution, the Fe and Fe in the 1M HCl solution were monitored every 5 days using the o-phenanthroline spectrophotometer. 2+ The monitoring time is 20 days. The monitoring results are as follows: After adding the corrosion inhibitor Ger-Cur, the Fe and Fe 2+ The content of Fe and Fe 2+ The contents were 0.27g and 0.11g, respectively, which were lower than the 0.71g Fe and 0.39g Fe released by the CK group. 2+ , indicating that the Ger-Cur treatment group has a certain corrosion inhibition effect.
[0026] Example 4 A green composite corrosion inhibitor Chi for inhibiting carbon steel corrosion, the composition and concentration of which are: chitosan 1.5 mM. A hydrochloric acid solution containing the corrosion inhibitor Chi is prepared according to the weighing and proportioning method of Example 1, a Q235 carbon steel sheet is placed in the hydrochloric acid solution, and the weight loss of the Q235 carbon steel sheet is monitored every 5 days for 15 days. Compared with the control group, the addition of the corrosion inhibitor has a significant corrosion inhibition effect on the Q235 carbon steel sheet in 1M HCl, and the average corrosion inhibition rate is 56.64% at 15 days.
[0027] After adding the corrosion inhibitor Chi to the 1M HCl solution, the Fe content in the 1M HCl solution was monitored every 5 days using the o-phenanthroline spectrophotometer method for 20 days. The monitoring results are as follows: After adding the corrosion inhibitor, the Fe content released into the solution by Q235 carbon steel also increases with time. The Fe content released by the corrosion inhibitor treatment group is 0.3008g, which is lower than the Fe content released by the CK group of 0.5716g, indicating that the treatment group has a certain corrosion inhibition effect.
[0028] Example 5 A green composite corrosion inhibitor Ger for inhibiting carbon steel corrosion, the composition and concentration of which are: 2 mM geraniol. A hydrochloric acid solution containing the corrosion inhibitor Ger is prepared according to the weighing and proportioning method of Example 1, a Q235 carbon steel sheet is placed in the hydrochloric acid solution, and the weight loss of the Q235 carbon steel sheet is monitored every 5 days for 15 days. Compared with the control group, the addition of the corrosion inhibitor has a significant corrosion inhibition effect on the Q235 carbon steel sheet in 1M HCl, and the average corrosion inhibition rate is 54.78% at 15 days.
[0029] After adding the corrosion inhibitor Ger to the 1M HCl solution, the Fe content in the 1M HCl solution was monitored every 5 days using the o-phenanthroline spectrophotometer method for 20 days. The monitoring results are as follows: After adding the corrosion inhibitor, the Fe content released into the solution by Q235 carbon steel also increases with time. The Fe content released by the corrosion inhibitor treatment group is 0.1917 g, which is lower than the Fe content released by the CK group of 0.4489 g, indicating that the treatment group has a certain corrosion inhibition effect.
[0030] Example 6 A green composite corrosion inhibitor Cur for inhibiting carbon steel corrosion, the composition and concentration of which are: 1.5 mM curcumin. A hydrochloric acid solution containing the corrosion inhibitor Cur is prepared according to the weighing and proportioning method of Example 1, a Q235 carbon steel sheet is placed in the hydrochloric acid solution, and the weight loss of the Q235 carbon steel sheet is monitored every 5 days for 15 days. Compared with the control group, the addition of the corrosion inhibitor has a significant corrosion inhibition effect on the Q235 carbon steel sheet in 1M HCl, and the average corrosion inhibition rate is 65.84% at 15 days.
[0031] After adding the corrosion inhibitor Cur to the 1M HCl solution, the Fe content in the 1M HCl solution was monitored every 5 days using the o-phenanthroline spectrophotometer method for 20 days. The monitoring results are as follows: After adding the corrosion inhibitor, the Fe content released into the solution by Q235 carbon steel also increases with time. The Fe content released by the corrosion inhibitor treatment group is 0.2122g, which is lower than the Fe content released by the CK group of 0.4489g, indicating that the treatment group has a certain corrosion inhibition effect.
[0032] When the corrosion inhibitor was added into 1M hydrochloric acid at the concentration of 1.5-2 mM chitosan, 1.5-2 mM curcumin and 1.5-2 mM geraniol, it had a significant corrosion inhibition effect on carbon steel. The highest inhibition rate reached 71.54% at 20 days. The total iron in the solution without corrosion inhibitor was 4-5 times that of the solution with corrosion inhibitor Chi-Ger-Cur, indicating that the addition of corrosion inhibitor Chi-Ger-Cur inhibited the iron loss of Q235 carbon steel in hydrochloric acid and alleviated the corrosion of Q235 carbon steel to a certain extent.
[0033] The chitosan used in the present invention is mostly derived from the shells and skeletons of arthropods such as shrimps and crabs, as well as the cell walls of higher plants. Geraniol is also mainly extracted from many flowers and herbs in industry, and curcumin is mainly derived from a natural phenolic substance extracted from the rhizomes of ginger plants. Therefore, the three components of the corrosion inhibitor of the present invention have a wide range of sources, mainly from plants, and are low in cost, simple to prepare, safe, non-toxic, and biodegradable.
Claims
1. A green composite corrosion inhibitor for inhibiting carbon steel corrosion, characterized in that The composition is chitosan, curcumin and geraniol. Chitosan, curcumin and geraniol are mixed into a solution with concentrations of 1.5-2 mM chitosan, 1.5-2 mM curcumin and 1.5-2 mM geraniol.
2. A green composite corrosion inhibitor for inhibiting carbon steel corrosion according to claim 1, characterized in that: The concentrations were: chitosan 1.5 mM, curcumin 1.5 mM, geraniol 2 mM.